Loss of surface immunoglobulin expression precedes B cell death by apoptosis in the bursa of Fabricius (The Rockefeller University Press, 1995)
The vast majority of lymphocytes generated daily in the chicken bursa of Fabricius do not emigrate to the periphery but die in situ. Apoptotic cells in the bursa can be readily detected by the presence of fragmented DNA and by the large numbers of condensed cellular nuclei observed by electron microscopy. Consequently, most newly generated lymphocytes die by programmed cell death. We show that bursal cells divide rapidly and apoptotic cells are derived from rapidly dividing precursors. Analysis of the phenotype of bursal cells undergoing apoptosis demonstrated that cell death does not occur in the most mature bursal cell population and is therefore not random. High levels of surface Ig are expressed on bursal cells entering S phase of the cell cycle. In contrast, bursal cells in the early stages of apoptosis in vivo express very low to undetectable levels of surface Ig but were unequivocally confirmed as being of the B lineage by polymerase chain reaction (PCR) detection of rearranged Ig genes. Bursal cells induced to undergo apoptosis in vitro express high levels of surface Ig demonstrating that induction of apoptosis does not in itself induce a loss of surface Ig expression. Consequently, loss of surface Ig expression precedes bursal cell death by apoptosis in vivo, suggesting that maintenance of a threshold level of surface Ig may be a requirement for the continued progression of chicken B lymphocyte development in the bursa.